PENGARUH KONSENTRASI MEDIA SOYBEAN DAN 20 JENIS L- ASAM AMINO PADA PRODUKSI ANTI JAMUR, ITURIN A - Yuliar, Yuliar (Jurnal Teknologi Lingkungan, 2009)
Influence of soybean meal concentration and 20 kinds of L-amino acids in iturin A production. Theuse of chemical pesticides has caused serious environmental problems and thus the demandfor safer pesticides is increasing. One alternative is microbial pesticides that suppress fungaland bacterial of plant pathogens. Bacillus subtilis has been known as producer of lipopeptideantibiotics, like iturin A, plipastatin and surfactin. In this study, iturin A as an antifungal of planpathogens was produced on varieties of soybean meal concentration; i.e. 8%, 10%, 12%, and15% using B.subtilis RB14-CS.The result indicates that 8% soybean meal concentration produced the highest of iturin Aproduction ( 2469 mg L-1) compared to the others. Beside the effect of nitrogen source (soybean), the influence of 20 kinds of L-amino acids on an enhancement of iturin A productivitywere observed. The examined L-amino acids were L-ala, L-arg, L-asn, L-asp, L-cys, L-glu, L-gln,L-gly, L-his, L-ile, L-leu, L-lys, L-met, L-pro, L-phe, L-ser, L-thr, L-tyr, L-trp and L-val. The resultsshow that no one of them could improve the iturin A productivity on soybean meal medium.